Study on damage tolerance and remain fatigue life of shattered rim of railway wheels. (May 2021) - Cong, Tao; Liu, Xiaolong; Wu, Si; Zhang, Guanzhen; Chen, Erqing; Qian, Guian; Berto, Filippo
Highlights: Alumina inclusions inside the rims responsible for the shattered rim of railway wheel. Fatigue life of the shattered rim is over 10 7 in the range of very-high-cycle fatigue. Proposing a method attempting to evaluate fatigue damage tolerance and the remaining service life of the wheel. Abstract: The shattered rim on railway wheels is increasingly concerned in recent years. Based on the failure analysis, the mechanism of shattered rim was revealed. The contact stress distribution of wheel/rail with inclusions in the wheel was analyzed by ABAQUS. Then the stress field was imported into FRANC3D to simulate the crack propagation. It is found that the simulation results were in good agreement with those obtained experimentally from the actual shattered rim, which proves the availability of the simulation. Meanwhile, the influence of the size and location of the inclusions on the fatigue life of the wheel was evaluated. Based on the crack propagation curves obtained by simulation, the rolling contact fatigue damage tolerance analysis and remaining fatigue life assessment method of wheels were proposed.